The Study of Partial Discharge of a Decommissioned 11kV Rotating Machine - Waiwicha, Supisara; Monkolsatitpong, Suriya; Inwanna, Woranan; Vanijkirati, Parada; Jeenmuang, Siwakorn; Pattanadech, Norasage (My University, 2024)
Over time the insulation system of the stator winding in machinery will gradually lose electrical and mechanical strength due to factors such as thermal, electrical, ambient, and mechanical stressors. At a certain point, the material will deteriorate significantly to the extent that the insulation breaks down or cracks under normal operating voltages, due to transient electrical or mechanical situations. This paper presents a study of the stator winding insulation system of a decommissioned 11kV motor with the removed rotor, using offline PD measurement. The measurement results revealed PD signals in all three phases. The PRPD patterns indicate internal delamination discharge and discharge at stress control coating(S/C) and stress control grading which is occurring simultaneously. When the test voltage is increased to a certain point, the electric field stress in the stress control grading area becomes high enough to cause a gap-type discharge pattern, occurring between the press finger and the stress control grading area. Visual inspections also revealed spark discharge.
Keywords: Internal delamination discharge; Motor; Off-line partial discharge; Partial discharge; PRPD pattern; Stator winding